2011
DOI: 10.4028/www.scientific.net/amr.275.186
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behaviour of Titanium, Ti-6Al-4V (wt %) Alloy and Ti-47Al-2Cr (at %) Alloy Produced Using Powder Compact Forging

Abstract: Powder compact forging was used to produce bulk consolidated titanium and Ti-6Al-4V (wt %) and Ti-47Al-2Cr (at%) alloy disks from hydrogenated and dehydrogenated (HDH) and gas atomised powders (GA) powders (in the case of titanium and Ti-6Al-4V) and a mechanically milled powder (in the case of Ti-47Al-2Cr alloy). The bulk titanium and Ti-6Al-4V (wt %) alloy have been produced by forging of the powder compacts. The Ti-47Al-2Cr (at %) alloy was produced using canned powder compact forging of a Ti/Al/Cr composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Induction heating is a well-tried way of achieving rapid heating and has been used successfully in ferrous PM [10,11]. More recently, induction heating has been successfully used in titanium PM for sintering prior to forging [12,13] and for heating prior to forging in air [14].…”
Section: Introductionmentioning
confidence: 99%
“…Induction heating is a well-tried way of achieving rapid heating and has been used successfully in ferrous PM [10,11]. More recently, induction heating has been successfully used in titanium PM for sintering prior to forging [12,13] and for heating prior to forging in air [14].…”
Section: Introductionmentioning
confidence: 99%
“…The parameters used for tensile testing of the HIP and powder forged samples are also given in our previous papers [4,5], the high temperature (HT) tensile testing of the powder forged samples was done on the specimens having a gauge length of 8.5mm, with a strain rate of 1.88x10 -4 /sec. Scanning electron microscopy (SEM), X ray diffractometry (XRD), and optical microscopy techniques were used for the microstructural characterization of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Khan et al [11] used high velocity powder compacting technique to compact Ti-6Al-4V (wt pct) alloy powder and found that with a high ram velocity, a relative high density of~86 pct can be achieved. Thermomechanical powder consolidation techniques such as hot isostatic pressing (HIP), [12,13] powder compact forging (PCF) [14][15][16] , and powder compact extrusion (PCE) [17] have been used by several research groups to consolidate titanium/titanium alloy powders and titanium/alloying element/master alloy powder blends. These works showed clearly that such powder consolidation processes can achieve good mechanical properties which are comparable to those of ingot metallurgy titanium/titanium alloys with same compositions.…”
Section: Introductionmentioning
confidence: 99%